2013
DOI: 10.2514/1.b34704
|View full text |Cite
|
Sign up to set email alerts
|

Detonation Transition Around Cylindrical Reflector of Pulse Detonation Engine Initiator

Abstract: To achieve reliable transmission of detonation waves to a pulse detonation engine (PDE) combustor (detonation chamber), the authors propose a PDE initiator that uses a cylindrical reflector downstream of a predetonator exit. The detonation wave propagates around the reflector to change the wave shape in three transition stages: from a planar detonation wave in the predetonator to an expanding cylindrical detonation wave, from the cylindrical wave to a planar toroidal detonation wave, and from the toroidal wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Previous detonation experiments 5,6 showed that detonation waves tend to propagate as roughly planar waves that diffract at sharp external corners. Within the diffracted portion of the detonation wave, the combustion decouples from the pressure wave and transitions to deflagration.…”
Section: Introductionmentioning
confidence: 98%
“…Previous detonation experiments 5,6 showed that detonation waves tend to propagate as roughly planar waves that diffract at sharp external corners. Within the diffracted portion of the detonation wave, the combustion decouples from the pressure wave and transitions to deflagration.…”
Section: Introductionmentioning
confidence: 98%
“…More work could be invested into transitioning the detonation wave from the detonation tube into the test section. While the detonation inside of the tube is predominantly a planar wave, when it diffuses at the exit of the tube, it becomes more of a cylindrical detonation wave [85]. Rather than a simple expansion of the detonation tube into the combustion channel, shock shapers and other tricks could be used to match the shape and profile to be more similar to that of what propagates in the FSRDE.…”
Section: Chapter 7: Recommendations For Future Workmentioning
confidence: 99%